Development of Local Culture-Based Interactive Media to Improve Children's Mathematics Skills in Kindergarten - Kurnia Gusni; Farida Mayar; Rakimahwati; Delfi Eliza (Jurnal Penelitian Pendidikan IPA, 2026)
This study addresses the limited development of early childhood mathematical abilities, which is often associated with the use of conventional learning approaches and the lack of innovative, technology-based instructional media. The objective of this research is to develop and evaluate local culture-based interactive animated video media to enhance early childhood mathematics skills. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was validated by experts in media, materials, and culture, followed by limited and broader trials involving children aged 5–6 years at Mekar Melati Kindergarten. Data were collected through validation sheets, observation, questionnaires, and pretest–posttest instruments, and analyzed using descriptive statistics and N-Gain scores. The results indicate that the developed media achieved a very high level of validity, with media validation at 100%, cultural validation at 93.75%, and material validation at 98.33%. The practicality test showed a score of 92.5%, indicating that the media is highly feasible for classroom use. Furthermore, the effectiveness test revealed a significant improvement in children's mathematical abilities, with an N-Gain score of 0.768 categorized as high. The findings also demonstrate that integrating local cultural elements into interactive media enhances children's engagement, conceptual understanding, and contextual learning experiences. In conclusion, local culture-based interactive animated video media developed through the ADDIE model is proven to be valid, practical, and effective in improving early childhood mathematics skills. This study highlights the importance of integrating technology and cultural context in early childhood education to support meaningful and engaging learning processes.